2021
DOI: 10.3390/metabo11080547
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Thermotolerance and Growth Performance in Chinook Salmon: Blood Biochemistry and Immune Capacity

Abstract: Ocean warming and extreme sea surface temperature anomalies are threatening wild and domesticated fish stocks in various regions. Understanding mechanisms for thermotolerance and processes associated with divergent growth performance is key to the future success of aquaculture and fisheries management. Herein, we exposed Chinook salmon (Oncorhynchus tshawytscha) to environmentally relevant water temperatures (19–20 °C) approaching their upper physiological limit for three months and sought to identify blood bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 65 publications
6
10
0
Order By: Relevance
“…Within an individual lifetime, its performance such as growth rate, can be altered through acclimation to environmental temperature, exhibiting a phenotypic plasticity pattern. These results align with a study on chinook salmon ( Oncorhynchus tshawytscha ) growth performance metrics during a three-month thermal challenge at 19–20 °C 32 . Schram et al 33 .…”
Section: Discussionsupporting
confidence: 89%
“…Within an individual lifetime, its performance such as growth rate, can be altered through acclimation to environmental temperature, exhibiting a phenotypic plasticity pattern. These results align with a study on chinook salmon ( Oncorhynchus tshawytscha ) growth performance metrics during a three-month thermal challenge at 19–20 °C 32 . Schram et al 33 .…”
Section: Discussionsupporting
confidence: 89%
“…While both TAC and LP indicate levels of oxidative stress, LP captures the effects of reactive oxygen species (ROS) on polyunsaturated fatty acids critical for growth in juvenile bivalves, but is also related to how metabolically active an organism is, which may not necessarily mean the organism is under stress (Gallager et al 1986;Lulijwa et al 2021;Lushchak 2011). Differences in the conditions experienced by mussel spat among sites and depths influenced TAC, but LP in this study indicated that although factors such as temperature, oxygen, and nutrient availability (Dowd et al 2013;Nogueira et al 2017;Viarengo et al 1995;Wilhelm Filho et al 2001) may have varied among sites and depths causing oxidative damage, the effects of ROS on lipid production was unaffected by these experimental treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A higher level of selenium micronutrient also plays a vital role in the stability of proteins (Schrauzer, 2003;Sahin et al, 2014). The reduction in total protein levels at the end of thermal shock may also indicate an increase in anaerobic metabolism and protein catabolism, which may predispose sh to death (Islam et al, 2020b;Lulijwa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%